187. Regional Distribution of Antimicrobial Resistance Among Outpatient Urine e. Coli Isolates in US Females ≥12 Years of age: a Multicenter Evaluation in 2019. (31st December 2020) - Kaye, Keith S; Gupta, Vikas; Mulgirigama, Aruni; Joshi, Ashish V; Scangarella-Oman, Nicole; Yu, Kalvin; Boyles, Anthony; Mitrani-Gold, Fanny S
Abstract: Background: The 2019 CDC Threats Report lists extended spectrum β-lactamase (ESBL) producing Enterobacterales as a serious health threat. While the clinical epidemiology of uncomplicated urinary tract infection (uUTI) has remained stable, there has been a notable increase in antimicrobial resistance (AMR) among community-acquired uUTIs. Urine cultures are seldom ordered for uUTI as treatment is often empiric; local surveillance data may therefore be lacking. The study objective was to determine the prevalence and geographic distribution of AMR in urine E. coli isolates from females in the US outpatient setting. Methods: A retrospective cross-sectional study of E. coli ambulatory urine isolates identified from females (≥ 12 years of age) at 296 facilities, with ≥ 1 quarter of data in 2019 (BD Insights Research Database, Franklin Lakes, NJ). Initial isolates representing each distinct susceptibility pattern within 30 days of index urine were included. E. coli isolates were identified as not-susceptible (NS) if intermediate/resistant to trimethoprim-sulfamethoxazole (TMP-SMX), fluoroquinolone (FQ), nitrofurantoin (NFT), ESBL+ (by commercial panels or intermediate/resistant to ceftriaxone, cefotaxime, ceftazidime or cefepime), and multi-drug resistant, defined as NS to ≥ 2 or ≥ 3 of FQ, TMP-SMX, NFT or ESBL+. Logistic regression models were used to evaluate resistance prevalence and variation across US census regions. Results: Of 267, 524 non-duplicate E. coli isolates evaluated, 25.1% (67, 189) were TMP-SMX NS, 20.3% (54, 359) were FQ NS, 7.3% (19, 576) were ESBL+, 3.5% (9, 453) were NFT NS, 14.0% (37, 328) were NS to ≥ 2 drugs and 4.0% (10, 814) were NS to ≥ 3 drugs. For all phenotypes, there was significant variation in resistance across census regions (all P< 0.001) with the highest in the East South Central region and lowest in the New England region of the US (Table). The figure shows regional prevalence of ESBL+ E. coli in 2019. Table. Antimicrobial resistance data from 30-day non-duplicate urine E. coli isolates in females ≥12 years old in 2019, by US census region. Figure. Heat map of the overall US geographic distribution of ESBL+ E. coli (30-day non-duplicate urine isolates) from females across 296 acute care facilities in 2019. Conclusion: The 2019 prevalence of AMR in non-duplicate ambulatory E. coli urine isolates was notable: TMP-SMX NS and FQ NS were > 20%. In addition, there were significant regional differences in resistance, with the highest in the East South Central region of the US, for all NS phenotypes. These analyses inform, and may optimize, empiric treatment of uUTI and patient outcomes. Disclosures: Vikas Gupta, PharmD, BCPS, Becton, Dickinson and Company (Employee, Shareholder)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Aruni Mulgirigama, MBBS, GlaxoSmithKline plc. (Employee, Shareholder) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder) Nicole Scangarella-Oman, MS, GlaxoSmithKline plc. (Employee, Shareholder) Kalvin Yu, MD, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Anthony Boyles, MSc, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder)